10 The effects of opioids on cognition in older adults with cancer and chronic non-cancer pain: a systematic review. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Pask, S; Dell'Olio, M; Murtagh, FEM; Boland, JW
Abstract : Background: Pain is poorly managed in older adults and opioids can be used to manage moderate-severe pain. Little data exists about adverse effects of opioids in this population, especially on cognition. Aim: To identify, appraise and synthesise evidence on the impact of opioids on cognition in older adults with cancer/chronic non-cancer pain. Methods: Protocol followed the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P). Searches of MEDLINE, EMBASE, PsycINFO, CINAHL, Cochrane Library and Web of Science, from inception to April 2018. Randomised controlled trials, quasi-experimental studies and observational studies of adults aged ≥65 with cancer/chronic non-cancer pain taking opioids were included. Measure(s) of cognition was the primary outcome. Study eligibility for inclusion, data extraction and quality appraisal (using QualSyst) were independently performed in duplicate. A narrative synthesis was conducted. Results: From 3370 unique articles screened, 12 met inclusion criteria. Studies explored cognition in 1134 participants with cancer and 959 with chronic non-cancer pain. Five studies reported no significant effect of opioids on cognition, two reported an improvement to cognition, three showed worsened cognition and two studies reported mixed effects. Studies showing improved cognitive function administered opioids over a short-term period, whilst those demonstrating decreased function administered opioids long-term. Higher opioid doses over long time periods led to decreased cognitive function. However, methods of cognitive assessment varied across studies (i.e. number of cognitive assessments used, cognitive domains assessed and timing). Six studies adopted single screening tools, which are not sensitive to detect subtle cognitive changes. Conclusion: To determine cognitive effects of opioids in this population, it is essential to report length of opioid use/dose, and the timing/sensitivity of screening tools and neuropsychological assessments. Without this evidence, we know little about how and whether adverse effects of opioids impact on pain management among older adults.